The Larval Density of Mosquitos (Diptera: Culicidae) in Jiaxiang County, Shandong Province, China: Influence of Bacterial Diversity, Richness, and Physicochemical Factors - Wang, Haiyang; Wang, Yang; Cheng, Peng; Wang, Huaiwei; Wang, Haifang; Liu, Hongmei; Zhang, Chongxing; Gong, Maoqing (Frontiers in Ecology and Evolution, 2021)
As Jiaxiang County of Shandong province is an area with complex mosquito vector composition, it is necessary to investigate the relationship between bacterial diversity, physicochemical factors, and larval density. Therefore, the physicochemical properties of 46 breeding sites for six kinds of habitat types (small puddles, small water containers, paddy fields, large water containers, irrigation channels, drainage ditches) were investigated by a multiparameter analyzer; the water's bacterial diversity was analyzed by the 16S rRNA full-length sequencing method. Spearman correlation and multiple linear regression were used to analyze the correlation between larval density and variables. The variables analyzed were dissolved oxygen, pH, hardness, turbidity, conductivity, temperature, ammonia nitrogen, water depth, and distance from the nearest house. One-Way ANOVA was used to understand whether there are differences in bacterial diversity in different habitats. Pearson linear correlation model was used to analyze the effects of bacterial diversity and abundance on mosquito densities in breeding sites. A total of 3291 larvae were captured, and a total of 6 species of 4 genera were identified. The identified species were Culex pipiens pallens, Aedes albopictus, Anopheles sinensis, Culex tritaeniorhynchus, Culex bitaeniorhynchus, and Mansonia uniformis. The density and species can be jointly affected by physicochemical properties and bacterial diversity, especially Shannon index and distance from the nearest house. In general, the physicochemical parameters and bacterial diversity of different habitats were significantly different. Even for the same habitat type, the physicochemical parameters varied greatly due to different environments.